The complete mitochondrial genome of Euonymus alatus (celastraceae, Euonymus L.). Issue 1 (2nd January 2021) - Zhang, Ting-Ting; Sun, Jing; Xu, Liang; Yang, Yan-Yun; Zhan, Zhi-Lai; Xing, Yan-Ping; Zhao, Rong; Li, Sheng-Nan; Zhang, Da-Chuan; Kang, Ting-Guo
Abstract: The complete mitochondrial genome of medicinal plant, Euonymus alatus, was sequenced for the first time. The genome sequence is 1, 045, 106 bp in length (GenBank accession number MW009108), with 44.98% GC contents. There are 72 genes in the genome, including 41 known protein-coding genes (PCGs), 22 transfer RNAs (tRNAs), and three ribosomal RNAs (rRNAs). The phylogenetic trees of 28 species are constructed using the maximum-likelihood method. The information will provide references for phylogenetic research.